Study on Treatment of Slaughterhouse Wastewater by Electro-coagulation Technique - B. Budiyono; I Nyoman Widiasa; Seno Johari (Chemical Engineering Diponegoro University, 2010)
Electro-coagulation (EC) is well known as a technique for removing suspended solids as well as oils and greases from wastewater. The aims of this research are to study the performance of the EC technique to treat a high strength wastewater from slaughterhouse in batchwise mode. The effect of various process variables such as number and electrode material, initial pH, suspended solid (SS) content, and operating time was investigated The electrolytic cell (electro-coagulator) used was a 600 ml cylinder glass reactor with working volume 400 ml and equipped by magnetic stirrer without temperature control. Cast iron (Fe) and aluminum (Al) cylinder were used as anode/cathode pair. The number of electrode was varied 1 and 2 pairs. The effective area of the electrode pair was 6.28 cm2. The DC power supply was controlled by a voltmeter and be adjusted constant at 125 A/m2 for each test runs. The initial SS concentration were varied from 1250, 2100, 3000, and 4000 mg/L by diluting wastewater. It is found that effluent temperature depends on SS and increases up to 98 °C when SS content was 4000 mg/L. One and two pairs of Fe-Al electrode will give SS removal efficiency are 97.2 and 99.6 %, respectively. However, the higher electrode number will need the shorter time to get certain removal efficiency of SS. Number of electrodes didn’t give the significant impact to the final pHs. With initial pH 7.05 both two pair of electrode will give the final pH relatively constant to 7.80. Further work will be conducted to optimize the CD and charge loading to avoid the excessive temperature increase